Pengaruh Penerapan E-Filing, Self Assessment System, dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Pada Kantor Pelayanan Pajak Pratama Kota Pangkalpinang Tahun 2020-2021) - Velenshia Corina; Novika Novika; Zamhari Zamhari (Politeknik Negeri Bengkalis, 2023)
This study aims to determine the effect of implementing E-Filing, Self Assessment System, and Tax Socialization on Individual Taxpayer Compliance (Study at the Pangkalpinang City Pratama Tax Service Office 2020-2021). This study uses quantitative methods. The population in this study were Individual Taxpayer which registered at KPP Pratama, Pangkalpinang. The sampling was conducted by Simple Random Sampling Method. The number of samples was determined by the researcher purposively with total of sample are 100 Individual Taxpayer. Data sources in this study use primary data with Quantitative Descriptive Method where the data collection were used in this study is survey methods with questionnaires as survey instrument. The data analysis technique used in this study is Multiple Linear Regression analysis tecniques. The results showed that Implementation of e-filing have a positive and significant effect on the level of Taxpayer Compliance. Self Assessment System have a positive and significant effect on the level of Tax Compliance. Tax socialization have a positive and significant effect on the level of Taxpayer Compliance. Implementation of e-filing, Self Assessment System and Tax socialization have a positive and significant effect together on the Taxpayer Compliance Level.Keywords: Implementation of E-filing, Self Assessment System, and Tax Socialization, Individual TaxpayerÂ Compliance